Modeling Short Term Interest Rates Using the Vasicek and Cox–ingersoll–ross Models - Md Sa’at A. S.; Shair S. N.; Md Lazam N.; Yusof A. Y.; Mohd Amin M. N.; Rose Irnawaty Ibrahim; Mohd Ghani N. A. (Lviv Polytechnic National University, Ukraine, 2025)
Index (Tier 2)